2005
DOI: 10.1097/01.wnq.0000173450.16339.77
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase, Catalase, and Guanase in Traumatic Brain Injury

Abstract: Objectives: Reactive oxygen species generated after brain trauma trigger a cascade of events resulting in neuronal death. Despite numerous defenses, the brain is vulnerable to oxidative damage, mainly because of its high content of unsaturated fatty acids. The goal in this experimental study was to demonstrate the activities of antioxidant enzymes, namely, superoxide dismutase, catalase, and guanase, in plasma and brain tissue at 30 minutes and 60 minutes after brain trauma.Methods: Forty adult male Sprague-Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These analyses showed the presence of classical neurotrophins and neuroprotective cytokines including BDNF, EGF, HGF, VEGF, PDGF, a neuron and glial growth regulator (glia maturation factor beta), 29 less known neuroprotective factors (TIMP-1, Neurabin-2 etc. ), antioxidative agents (catalase, glutathione S-transferases, SOD, guanase), 30 and anti-inflammatory molecules TGF-β, fibroblast growth factor (FGF), insulin-like growth factor (IGF), etc. This is in line with previous characterization of the HPPL by ELISA that established its high contents of neurotrophic, angiogenic, and anti-inflammatory growth factors such as PDGF, BDNF, β-FGF, VEGF, and TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses showed the presence of classical neurotrophins and neuroprotective cytokines including BDNF, EGF, HGF, VEGF, PDGF, a neuron and glial growth regulator (glia maturation factor beta), 29 less known neuroprotective factors (TIMP-1, Neurabin-2 etc. ), antioxidative agents (catalase, glutathione S-transferases, SOD, guanase), 30 and anti-inflammatory molecules TGF-β, fibroblast growth factor (FGF), insulin-like growth factor (IGF), etc. This is in line with previous characterization of the HPPL by ELISA that established its high contents of neurotrophic, angiogenic, and anti-inflammatory growth factors such as PDGF, BDNF, β-FGF, VEGF, and TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an increasing trend of SOD and catalase proportional to the severity of head trauma, indicating the presence of SOD interactions and catalase as antioxidant enzymes with ROS for cell protection. 20 Damage to brain tissue due to head trauma was also related to the demyelination process, which causes long-term cognitive deficits and sensorimotor. Oligodendrocytes as the primary cells responsible for producing and maintaining the myelin membranes under normal conditions and remyelination after axonal damage are highly sensitive to both ischemic and traumatic situations.…”
Section: Original Articlementioning
confidence: 99%
“…Their study also reported a concomitant increase in stress proteins, known to trigger inflammation, signifying the role of SOD and CAT in neuroprotection against oxidative stress. The high levels of unsaturated lipids and fatty acids present in neuronal cells make them highly susceptible to oxidative damage (74). …”
Section: Drugs and Drug Delivery Systemsmentioning
confidence: 99%